Aspirin and Other Non-Steroidal Anti-Inflammatory Drugs as Cyclooxygenase Inhibitors: State of the Art, Barriers and Perspectives - Avram, Speranta; Duda-Seiman, Daniel M.; Svab, Istvan; Mancas, Silvia; Duda-Seiman, Corina; Mihailescu, Dan F. (Current Computer - Aided Drug Design, 2009)
Non-steroidal anti-inflammatory drugs (NSAIDs) claimed during last years an increased research interest to establish their cardiovascular safety profile. Generally, NSAIDs inhibit in different degrees both isoforms of cyclooxygenase (COX). Aspirin has a unique property among NSAIDs, namely at low doses it inactivates irreversibly the COX-1 activity in platelets. It is well known that platelets are a significant source of inflammatory mediators and their activation leads to important clinical atherothrombotic vascular events. Atherosclerosis is a chronic inflammatory process. The cardioprotective effect of aspirin resides in it's mechanism of action, suppressing the platelet COX-1 dependent thromboxane biosynthesis. There are patients who do not benefit from the cardioprotective effect of aspirin, being labeled as “resistant” to aspirin. The underlying mechanism of aspirin resistance is yet unclear. This review intends to detail recent advances in the field of molecular simulation applied to nonselective non-aspirin NSAIDs and other COX selective inhibitors. Binding studies were performed between the COX-2 enzyme and these molecules. Using 2D-QSAR, it was noticed that the lipophilic bulkier group width-wise is required for a significant biological activity and also, the hydrophobic interactions might be crucial for the potency of same COX inhibitors. In order to understand a meaningful comparison of both classical NSAIDs and newer COX-2 inhibitors, three-dimensional quantitative structure-activity relationships and also molecular docking techniques were applied.
Keywords: molecular simulation